Citizens of the Future: Beyond Normative Conditions through the Emergence of Desirable Collective Properties - Bendek, Zoraida Mendiwelso (Journal of business ethics, 2002)
In this paper I explore the influence of an organisation's structure, such as that of the National Education System, in the emergence of desirable social properties. In this case the concern is schools with adequate performance. It is assumed that there is a circular causality between structure and the social results of schools. I highlight some of the structural requirements to have justice, sense of belonging, trust, honesty and cooperation as emerging properties of these schools, beyond normative statements. These are requirements for effective citizenship. In order to study this, it is necessary to observe the structures that constitute collectives into organisations. Central to this paper is a case study that I carried out at Millfield Primary School in the U.K., which focused on the observation of citizenship as a dynamic process permanently being constructed. This case went beyond the normative understanding of citizenship as established in the new school curriculum to be implemented from September 2002. I take the view that the aim of citizenship is to build up a community in which one is constituted as a citizen. For that purpose we need enabling people to build up their own communities. My conclusion from this case study suggests that current educational methodologies aim at teaching a "model of" citizenship rather than at providing the necessary tools to think about and create suitable spaces "for" citizenship. The case study shows that it is necessary to reinforce in schools practical methods to create membership and respect for others.